2012
DOI: 10.1186/1471-2407-12-80
|View full text |Cite
|
Sign up to set email alerts
|

Polo-like kinase 1 (PLK1) inhibition suppresses cell growth and enhances radiation sensitivity in medulloblastoma cells

Abstract: BackgroundMedulloblastoma is the most common malignant brain tumor in children and remains a therapeutic challenge due to its significant therapy-related morbidity. Polo-like kinase 1 (PLK1) is highly expressed in many cancers and regulates critical steps in mitotic progression. Recent studies suggest that targeting PLK1 with small molecule inhibitors is a promising approach to tumor therapy.MethodsWe examined the expression of PLK1 mRNA in medulloblastoma tumor samples using microarray analysis. The impact of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
67
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 34 publications
12
67
0
Order By: Relevance
“…None of these trials have specifically addressed the possibility that PLK1 inhibitors may be beneficial for the treatment of brain tumors. Our group has demonstrated that PLK1 inhibitors could be used to target glioblastoma (18,40) and another group has published data agreeing with our findings in medulloblastoma (41,42). We illustrate that PLK1 is a promising drug target for medulloblastoma because (i) it is highly expressed in tumors relative to normal brain tissues and (ii) there are small molecule inhibitors that suppress primary medulloblastoma cells and cell lines in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 76%
“…None of these trials have specifically addressed the possibility that PLK1 inhibitors may be beneficial for the treatment of brain tumors. Our group has demonstrated that PLK1 inhibitors could be used to target glioblastoma (18,40) and another group has published data agreeing with our findings in medulloblastoma (41,42). We illustrate that PLK1 is a promising drug target for medulloblastoma because (i) it is highly expressed in tumors relative to normal brain tissues and (ii) there are small molecule inhibitors that suppress primary medulloblastoma cells and cell lines in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 76%
“…PLK1 is the best characterized member in the PLK family, and increasing evidence suggests that PLK1 serves as a good candidate for cancer drug targeting in several malignancies; various PLK1 inhibitors are efficacious as anticancer drugs (18,32,33). A previous study showed that inhibition of PLK1 function suppresses cell growth and increases radiation sensitivity in medulloblastoma cell lines (34). In a diffuse large B-cell lymphoma study, a small-molecule PLK1 inhibitor, MLN0905, was confirmed to have antitumor effects (35).…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Synergistic effects on clonogenicity have been demonstrated in rectal tumor cells using PLK1 inhibition by siRNA combined with radiation, 26 this approach has also been effective on head-and-neck squamous cell carcinoma. 30 Comparatively, the pharmacological inhibition of PLK1 by BI 2536 has shown to radiosensitize medulloblastoma cells, 31 whereas GSK461364A-sensitized tumor cells to radiation and prevented the growth of metastatic breast cancer cells. 32 The development of drug resistance is a common problem in treatment of bladder cancers.…”
Section: Methodsmentioning
confidence: 99%